2013
DOI: 10.1016/j.rmed.2013.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Fluticasone/formoterol dry powder versus budesonide/formoterol in adults and adolescents with uncontrolled or partly controlled asthma

Abstract: ISRCTN60408425).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…These two studies were designed to assess non-inferiority of the FP/F combination in comparison with the other comparator combinations used at equivalent doses (Table 3). Both studies showed that the FP/F combination and the comparators had an equivalent effect in term both of pre-dose between-group differences were observed with regards to exacerbation rates and adverse events [26].…”
Section: Fp/f Versus Other Combinationsmentioning
confidence: 98%
“…These two studies were designed to assess non-inferiority of the FP/F combination in comparison with the other comparator combinations used at equivalent doses (Table 3). Both studies showed that the FP/F combination and the comparators had an equivalent effect in term both of pre-dose between-group differences were observed with regards to exacerbation rates and adverse events [26].…”
Section: Fp/f Versus Other Combinationsmentioning
confidence: 98%
“…Many clinical studies have demonstrated the superiority of FF to either component administered as a monotherapy or concurrently via separate inhalers [ 19 , 20 ]. Similarly, the FF combination has been proven to have similar efficacy and safety profiles compared to budesonide/formoterol and fluticasone-salmeterol [ 9 , 21 ]. FF offers an additional benefit of rapid bronchodilation than fluticasone-salmeterol [ 7 , 8 ].…”
Section: Formoterol-fluticasone Single Inhaler: Available Evidencementioning
confidence: 99%
“…The study by Rafferty et al (1985) was a double blinded crossover study which compared between beclomethasone dipropionate (BOP) and budesonide and concluded that there was no difference in their outcomes. Moreover, a recent article in press by Cukier et al (2013) compared between inhaled fluticasone versus budesonide inhalers, both were combined with long acting beta 2 agonist formoterol. The study included adults and adolescents with uncontrolled or partially controlled asthma and the superiority of fluticasone over budesonide was noted in terms of lung function and asthma control.…”
Section: Domain B: Prescribing Effectively Safe Professional and Alwmentioning
confidence: 99%